Transcription-associated mutagenesis increases protein sequence diversity more effectively than does random mutagenesis in Escherichia coli. - Hyunchul Kim (PLoS ONE, 2010)
BACKGROUND: During transcription, the nontranscribed DNA strand becomes single-stranded DNA (ssDNA), which can form secondary structures. Unpaired bases in the ssDNA are less protected from mutagens and hence experience more mutations than do paired bases. These mutations are called transcription-associated mutations. Transcription-associated mutagenesis is increased under stress and depends on the DNA sequence. Therefore, selection might significantly influence protein-coding sequences in terms of the transcription-associated mutability per transcription event under stress to improve the survival of Escherichia coli. METHODOLOGY/PRINCIPAL FINDINGS: The mutability index (MI) was developed by Wright et al. to estimate the relative transcription-associated mutability of bases per transcription event. Using the most stable fold of each ssDNA that have an average length n, MI was defined as (the number of folds in which the base is unpaired)/nx(highest -DeltaG of all n folds in which the base is unpaired), where DeltaG is the free energy. The MI values show a significant correlation with mutation data under stress but not with spontaneous mutations in E. coli. Protein sequence diversity is preferred under stress but not under favorable conditions. Therefore, we evaluated the selection pressure on MI in terms of the protein sequence diversity for all the protein-coding sequences in E. coli. The distributions of the MI values were lower at bases that could be substituted with each of the other three bases without affecting the amino acid sequence than at bases that could not be so substituted. Start codons had lower distributions of MI values than did nonstart codons. CONCLUSIONS/SIGNIFICANCE: Our results suggest that the majority of protein-coding sequences have evolved to promote protein sequence diversity and to reduce gene knockout under stress. Consequently, transcription-associated mutagenesis increases protein sequence diversity more effectively than does random mutagenesis under stress. Nonrandom transcription-associated mutagenesis under stress should improve the survival of E. coli.